A LEGAL PROCESS OF ADJUSTING OF PUBLIC LIFE IS IN MODERN UKRAINIAN SOCIETY - Кравченко, А. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the problem of adjusting of public life opens up in modern Ukrainian society by means of the effective legal system.